Targeting the 3D genome by anthracyclines for chemotherapeutic effects - Minkang Tan; Shengnan Sun; Yuchen Liu; Andrea A. Perreault; Douglas H. Phanstiel; Liping Dou; Baoxu Pang (Proceedings of the National Academy of Sciences, 2025)
The chromatin is folded into three-dimensional (3D) structures, and aberrant 3D chromatin folding has been implicated in cancer. We performed ATAC-seq and TOP2A ChIP-seq to assess the potential effects of various anthracycline drugs on the chromatin architecture. We found that specific anthracycline variants selectively disrupt chromatin looping anchors by interfering with CTCF binding, suggesting an additional therapeutic mechanism of anthracycline drugs targeting the 3D genome. Hi-C experiments in K562 cells treated with anthracycline drugs revealed widespread disruption of 3D chromatin organization, including altered long-range regulation at the Myc locus. Furthermore, AML patients treated with anthracycline drugs exhibited changes in chromatin structures near possible looping anchors, which were associated with distinct clinical outcomes. Together, our findings indicate that anthracycline drugs function as potent and selective epigenomic modulators, with the capacity to further target the 3D genome to exert anticancer effects, highlighting their potential for personalized therapy in tumors with aberrant 3D chromatin architecture.